1993
DOI: 10.1113/jphysiol.1993.sp019680
|View full text |Cite
|
Sign up to set email alerts
|

Roles of sympathetic nervous system in the suppression of cytotoxicity of splenic natural killer cells in the rat.

Abstract: SUMMARY1. We previously demonstrated that a central injection of interferon-a in rats induced a suppression of cytotoxicity of splenic natural killer cells which depended upon intact splenic sympathetic innervation, suggesting the important role of the splenic nerve in immunosuppression. To further study the mechanisms of this phenomenon, we investigated: (1) the effects of a central injection of recombinant human interferon-x on the electrical activity of the splenic nerve, and (2) the responses of splenic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
55
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 33 publications
(38 reference statements)
6
55
0
Order By: Relevance
“…3), but not into the PVN (Fig. 5), was effective in increasing the splenic nerve activity to the same degree as that observed after the intra-third ventricular injection at a dose of 1500 U in rats (Katafuchi et al 1993). Furthermore, we have found that the microinjection of 200 U interferon-a into the MPO reduced the splenic natural killer cell activity to the same degree as that observed after lateral cerebroventricular injection at a dose of 20000 U in rats (Take et al 1992b).…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…3), but not into the PVN (Fig. 5), was effective in increasing the splenic nerve activity to the same degree as that observed after the intra-third ventricular injection at a dose of 1500 U in rats (Katafuchi et al 1993). Furthermore, we have found that the microinjection of 200 U interferon-a into the MPO reduced the splenic natural killer cell activity to the same degree as that observed after lateral cerebroventricular injection at a dose of 20000 U in rats (Take et al 1992b).…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, we recently found that electrical stimulation of the splenic nerve for 20 min resulted in a suppression of the splenic natural killer cell activity, which was blocked by an i.v. injection of a peripherally acting f8-adrenergic blocking agent, nadolol, indicating a /8-adrenergic receptormediated suppression of the splenic natural killer cell activity (Katafuchi et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations